Profit for All: Modest Proposals for a Fatter Future - Jefford, Andrew (Petits Propos Culinaires, 2001)
This is the text of a talk by author and broadcaster Andrew Jefford given at the Food Festival in Abergavenny September 2001. It preserved it in its original form as spoken text in which he surveys the state of British food production with his tongue firmly in his cheek.